Cellular and physiological upregulation of inducible nitric oxide synthase, arginase, and inducible cyclooxygenase in wound healing. Issue 12 (3rd June 2019) - Abd El‐Aleem, Seham A.; Abdelwahab, Soha; AM‐Sherief, Hany; Sayed, Ahmed
Abstract: Wound repair is regulated by overlapping cellular, physiological and biochemical events. Prostaglandins and nitric oxide have been a focus for inflammation research particularly since the discovery of their inducible isoforms nitric oxide synthase (iNOS) and cyclooxygenase‐2 (COX‐2). Study of the cellular expression of iNOS and COX‐2 and arginase which competes with iNOS for its substrate, in an in vivo model of wound healing could reveal important roles for these enzymes in the physiological progression of wound repair. Adult male rats received full thickness dermal wounds which were harvested at different times. Protein levels and activities of the enzymes were assessed by western blot and biochemical assays respectively. The cellular distribution and the colocalization were assessed by immunostaining. The protein levels and activities of iNOS, arginase, and COX‐2 increased only during the inflammatory phase of wound. Immunocytochemistry showed that the three enzymes were coexpressed and the main cellular source was inflammatory cells mainly macrophages. iNOS was induced at the wound site and was the earliest to increase significantly ( p < 0.05) for only up to 3 days postwounding. However, arginase and COX‐2 significant ( p < 0.05) upregulation started at a later time points and continued for up to 14 days postwounding. Therefore iNOS, compared with arginase and COX‐2, showed a temporal difference in expression during wound healing which could be explained by their products being required at different stages of the healing process. The coordinated expression of the three enzymes at different time points could account for the physiological progression of the healing process. Abstract : Regulation of inducible nitric oxide synthase, arginase and inducible cyclooxygenase in wound healing.